THE INFLUENCE OF WORD OF MOUTH, CUSTOMER EXPERIENCE, AND RISK PERCEPTION ON PURCHASE DECISIONS FOR WARDAH PRODUCTS - Irfan Andinata; Nurlaila; Annio Indah Lestari Nasution (Pena Cendekia Insani, 2025)
The skincare industry has experienced rapid growth in line with increasing public awareness of the importance of skin care, particularly among younger generations. Skintific, a skincare brand based on dermatological research, faces intense competition, making it essential to understand the factors that influence consumer purchase decisions. This study aims to examine the effect of Word of Mouth (WOM), customer experience, and perceived risk on purchase decisions for Skintific products. A quantitative approach was employed, with data collected through questionnaires distributed to consumers who had previously used Skintific products. Multiple linear regression analysis was used to test the hypotheses. The results indicate that WOM, customer experience, and perceived risk have a positive and significant influence on purchase decisions, both individually and collectively. These findings suggest that positive WOM, satisfying customer experiences, and effective management of rerceived risk are crucial strategies to encourage consumer interest and purchasing decisions. The practical implications of this research highlight the need for Skintific to strengthen testimonial-based communication, improve the quality of customer interactions, and provide comprehensive product education to reduce consumer concerns.